THE EFFECT OF LOCUS OF CONTROL AND TIME MANAGEMENT ON ACADEMIC STRESS AMONG WORKING STUDENTS THROUGH PEER SOCIAL SUPPORT AS AN INTERVENING VARIABLE - Aras, Muhammad; Fitri, Dewi Wulan; Firman, Firman (Universitas Negeri Makassar, 2026)
This study examines the effects of locus of control and time management on academic stress among working students, with peer social support serving as an intervening variable. The study involved 169 working students selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The analytical procedures included validity and reliability testing, structural model analysis, and testing of direct and indirect effects. The findings indicate that locus of control and time management significantly influence academic stress, both directly and indirectly through peer social support. These results highlight the importance of strengthening personal self-regulation capacities and fostering supportive peer environments to reduce academic stress among working students. Keywords: Locus of Control, Time Management, Peer Social Support, Academic Stress, Working Student.